Plasma and Urinary Amino Acid Profile in Children with Infantile Tremor Syndrome. (7th August 2021) - Dileep Satya, K; Attri, Savita Verma; Sharawat, Indar Kumar; Vaidya, Pankaj C; Mehra, Nancy; Patial, Ajay; Sankhyan, Naveen; Singhi, Pratibha D
Abstract: Background: Infantile Tremor Syndrome (ITS) is a disorder of infancy, and characterized by developmental delay and/or regression, pallor, skin hyperpigmentation and hypopigmented hair. It is commonly seen in infants in whom exclusive breastfeeding is given inappropriately for longer durations than recommended. ITS is predominantly reported from the Indian subcontinent and in children from a lower socioeconomic background. It is a clinical diagnosis and vitamin B12 deficiency is the most commonly accepted etiology of this entity. Objectives: The primary objectives of study were to compare the plasma and urine amino acid levels among children with ITS spectrum with those of healthy children. The secondary objectives were to compare the plasma and urine amino acid levels among children with ITS and Pre-ITS. Study design: This cross-sectional, observational study was carried out at a tertiary care hospital in North India. Participants: A total of 50 children aged < 36 months with ITS/Pre-ITS were enrolled. Children with Pre-ITS and ITS were compared with healthy age-matched study subjects. Results: Thirty-nine (78%) cases and twelve (24%) healthy children had low serum vitamin B12 levels. Folate levels were normal in all the controls, while only one case had folate deficiency. There were significant differences ( p  < 0.05) in the values of 32 amino acids in plasma. Among 44 urinary amino acids, levels of 30 amino acids were significantly different in the cases compared with the controls ( p  < 0.05). Conclusions: Several changes in amino acids in the children suffering from ITS were observed. These changes may be a reflection of the metabolic derangements in ITS.